Cooperation between Mind, Body and Soul in Healing Trauma: Array - Ciucur (Frigioiu), Ștefania (New Trends in Psychology, 2020)
Although theoretically we humans belong to an extremely powerful species, enduring over time endless wars, natural or man-made disasters, losses, violence and personal betrayals, all these traumatic experiences have left marks both in history as well as on a personal or family level. At the same time, these marks permeate our minds and emotions, our ability to enjoy and experience happiness, and even our immune system and biology. Trauma affects not only those directly involved but also those around them, who are put under extra pressure, namely to give them their energy and strength in the desire to help them continue to function, despite the fact that they are overwhelmed by the memory of the pain and shame of going through those traumas.